Arouca Geopark: geotourists are arriving! - Rocha, Daniela (2013)
The Arouca Geopark, located in the Aveiro district (northern Portugal), originated in 2005 and was formally established in late 2007, under the auspices of Arouca's Municipal Chamber. This ongoing project will soon be submitted to the European and Global Geoparks Networks, making it the second Portuguese geopark inside these networks. During the last three years, an international multidisciplinary team has been working on the rich geodiversity of the area, promoting the inventory and characterization of 36 geological sites, together with the identification of biological and cultural heritage (archaeology, history, ethnography, gastronomy) which are necessary to fulfil the geopark requirements. The link with educational and tourist activities is also progressing, aiming the sustainable development of the region. Among the 36 geological sites subject to preliminary studies and already accessible, two of them are of special international relevance: the Canelas Slate Quarry and its on-site Museum, and the Castanheira Nodular Granite, with a place popularly known as pedras parideiras (= "the stones that give birth", or rather "rocks delivering stones"). The first is an outstanding fossil locality of Darriwilian (Middle Ordovician) age, where giant trilobites (up to 70 cm in size) and trilobite clusters (from several to thousands of specimens) occur in large slabs of shale, recovered during roofing slate quarrying. The Valerio & Figueiredo private company encourages scientific access to its quarry and has built an on-site museum to preserve and disseminate knowledge about trilobites and the Ordovician world. The Geological Interpretation Centre of Canelas, located near the quarry and open since 2006, is one of the main tourist attractions of the Arouca Geopark, having received more than 10,000 visitors in 2007. The Castanheira Granite is a small and very peculiar granite outcrop that contains a remarkable abundance of discoidal biotite nodules ranging from 1−12 cm in diameter, now protected by the Arouca municipality and visited by 15,000 persons during the last year. A popular legend attributes magical properties to these nodules in terms of female fertility, since these dark mineral lumps pop out spontaneously from a creamy-coloured matrix due to differential dilatation during the hot summers. A new interpretation centre will be established in 2008, using an old house close to the outcrop: the "House of Rocks Delivering Stones". The present work is being performed under the project "Identification, Characterization and Conservation of Geological Heritage: a Geoconservation strategy for Portugal" sponsored by the Portuguese Foundation of Science and Technology (PTDC/CTEGEX/64966/2006, years 2007-2009), and is also part of the PATRIORSI project of the Spanish Ministry of Education and Science (CGL2006- 07628/BTE, years 2006-2009).